PENGARUH TERAPI AKTIVITAS KELOMPOK TERHADAP PENURUNAN TINGKAT HALUSINASI PENDENGARAN PADA PASIEN SKIZOFRENIA - Italia; Hidayati, Nurul (LPPM STIKes Mitra Adiguna, 2025)
Schizophrenia is a syndrome with diverse causes, with a varied course of the disease, depending on a combination of genetic, biological, social, and cultural factors. Symptoms of schizophrenia are generally divided into two types, one is positive symptoms, which include hallucinations—perceptions that arise due to stimuli that are too strong to be processed normally—and delusions and impaired logical thinking. This study aims to determine the effectiveness of group activity therapy on reducing the level of auditory hallucinations in schizophrenia patients at the Mitra Mulia Husada Foundation in Palembang City in 2024. This study used a pre-experimental design with a one-group pretest-posttest approach without a control group. The results of the frequency distribution showed that the majority of respondents had a good lifestyle, namely 35 elderly people (62.5%), while those with a poor lifestyle were 21 elderly people (37.5%). Before the implementation of group activity therapy, the average hallucination score in the 20 respondents was 12.95. After being given the therapy, the average score increased to 13.75. Statistical test results showed a significant effect between group activity therapy and a reduction in the intensity of auditory hallucinations in schizophrenia patients (p-value = 0.002). Therefore, it is recommended that the Mitra Mulia Husada Foundation of South Sumatra Province integrate group activity therapy as part of a non-psychopharmacological intervention in nursing care for patients with auditory hallucinations.